Stuve-Wiedemann Syndrome: Is it Underrecognized? - GÜRAN, TÜLAY (WILEY, 2014)
Stuve-Wiedemann Syndrome (SWS) (OMIM #601559) is an autosomal recessive disorder characterized by skeletal changes, bowing of the lower limb, severe osteoporosis and joint contractures, episodic hyperthermia, frequent respiratory infections, feeding problems and high mortality in early life. It is caused by mutation in the leukemia inhibitory factor receptor gene (LIFR; 151443) on chromosome 5p13. We provide the clinical follow-up and molecular aspects of six new patients who carried the same novel mutation in the LIFR gene (p. Arg692X) and three patients carried a common haplotype at the LIFR locus supporting a founder effect in the Turkish population. The probable pathogenesis of the features is also discussed. Osseous findings in the presence of other above-mentioned morbid conditions should raise the suspicion of SWS in neonates especially in Arabic and Eastern Mediterranean countries with high rate of consanguineous marriages like in Turkey. Severe osteoporosis, bone deformities, milias, leukocoria, inflammatory lesions on distal extremities, tongue biting behavior and oral ulcers could be more prominent features of the survivors beyond the neonatal period while respiratory and feeding problems are remitting. It is of crucial importance to diagnose such babies earlier in order to prevent extensive laboratory workup and to provide proper genetic counseling. (C) 2014 Wiley Periodicals, Inc.
Keywords: Stuve-Wiedemann syndrome; LIFR; founder effect